Sexuality Landscape of Modern Kerala: A Discourse on Male Social Gathering among Malabar Muslim Men - T.K. Sulaiman (International Journal of Social Science, 2017)
An enquiry that would light on the past of sexuality and the ways in which the contemporary is of sexuality is produced through its historical legacies. Sexual topics of any kind are avoided in polite conversation in India, and any talk concerning homo-sociality (male social gathering) is altogether taboo, especially in Kerala (even kiss of love). Here how Malabar became popular for homo-sociality expedition and its nature and nurture is tracing out. Sketching the process of transformation from homo-sociality sub culture to a kind of gay politics in Calicut (Kozhikode) is the focus of the study.